The Effect of Direct Interaction Strategy in Teaching Reading Comprehension at the Tenth Grade of SMA Negeri Taekas in the Academic Year 2024/2025 - Sengkoen, Maria Gradiana; Misa, Mikhael; Seran, Yanuarius (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
This study aimed to examine the effect of the Direct Interaction Strategy on teaching reading comprehension of narrative texts at the tenth grade of SMA Negeri Taekas in the academic year 2024/2025. The research employed a quasi-experimental design with two groups: an experimental class that received instruction using the Direct Interaction Strategy and a control class that was taught using conventional teaching methods. Data were collected using pre-tests and post-tests to measure students' reading comprehension before and after the intervention.The findings reveal a significant improvement in the reading comprehension scores of the experimental class compared to the control class. The experimental group showed an increase from an average pre-test score of 43.6% (categorized as "Very Poor") to a post-test score of 89.86% ("Excellent"), marking a 106% improvement. In contrast, the control class, which was taught using conventional methods, showed minimal improvement, with an average score increase from 30% to only 28.26%, still categorized as "Very Poor." These results indicate that the Direct Interaction Strategy effectively enhances students’ comprehension of narrative texts by fostering engagement, encouraging critical thinking, and providing real-time feedback. The study concludes that implementing the Direct Interaction Strategy in teaching reading comprehension significantly benefits students' understanding of narrative texts. Therefore, it is recommended that educators incorporate this approach into their teaching practices to optimize students’ learning outcomes.